PESANTREN DALAM DINAMIKA - Amiruddin Mustam (IAIN PAREPARE, 2017)
Islamic education has been growing and developing along with the existence of Islam in Indonesia as an effort of Islamization, and as a process of growth and development of Islamic society in Indonesia. One form of Islamic education that was developed since the existence of Islam in the archipelago is Islamic boarding school. The current form of pesantren, in its history, is the development of the Prophet's period of education. namely: Khuttab and Khalaqah. In the development of pesantren, it has two functions, as a value transformation with amar ma'ruf nahi mungkar (classical function) and community development, as a means of improving living standards and community welfare (development function). As'adiyah pesantren since its foundation plays a role in the development of education in southern and eastern archipelago and serves as a printers of Islamic scholars and preservers. In this pesantren, becoming a scholar or kiai, santri are required to master various religious disciplines. Therefore, to reach the title of kiai (young kiai), not all santri can get it. A senior santri must first take a memorizing test from a kiai. The test results determine whether the kiai admit it or not. If it has been recognized by the kiai that the person is already worthy of being a young kiai. As'adiyah Boarding School's role is so great and make the government and community of Wajo district put hope to this pesantren to become one of change agent and community development. Thus, the demand is also for this pesantren, to be more responsive to the needs and challenges of the times.